Hypoglycaemic effect of a combination of Pleurotus ostreatus, Murraya koenigii and Aegle marmelos in diabetic rats - KRISHNA, SARITHA; USHA, P T A (The Indian Journal of Animal Sciences, 2011)
This study was conducted to assess the hypoglycaemic effect of a combination of Pleurotus ostreatus, Murraya koenigii and Aegle marmelos in alloxan induced diabetic rats. A combination of P. ostreatus (250 mg/kg), M. koenigii (250 mg/kg) and A. marmelos (250 mg/kg) was administered orally to diabetic rats and the effects were compared with individual plant extracts. The study revealed that the combination produced synergistic effects on lowering of blood glucose levels, serum cholesterol and triglyceride levels when compared to individual plant extracts. The effect of the combination was comparable to the reference drug glibenclamide.